FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN KANKER SERVIKS - Dinni Eka Yuliani; Yuniarti Yuniarti; Jubaidi Jubaidi (Poltekkes Kemenkes Bengkulu, 2021)
Cervical cancer is the number one cause of death in the world from all existing cancer. Data RSUD Dr. M. Yunus Bengkulu in 2016 as many as 34 people with cervical cancer. Not performing regular early detection is the biggest factor causing cervical cancer. The purpose of this study was to determine the factors that affect the incidence of cervical cancer in Dr. M. Yunus City of Bengkulu Year 2016.The type of this research is mixed method. Quantitative samples were 34 cases and 68 controls used secondary data and primary data while the qualitative data were 3 main informants and 2 supporting informants using in-depth interviews. This research was conducted in December 2017 - January 2018 at Dr.. M. Yunus Bengkulu.The results showed that there were age relationship (p = 0,016), married age (p value = 0,036), parity (p value = 0,005), hormonal contraceptive use (p value = 0,033) and no job relation with cervical cancer incidence p = 0.249). Multivariate analysis result of age factor become the dominant factor influencing cervical cancer with P value 0,001 and OR 8,312. While qualitative got 2 out of 3 informant have sexual intercourse first age less than 20 year, 1 of 3 informant have sexual relationship outside of marriage, 2 out of 3 informant have sexual partner more than than, 1 of 3 informant have couple sekksual at risk, 2 of 3 respondents married more than once.Health officers as a counselor should increase the knowledge and understanding of the public about cervical cancer through extension activities to reduce the incidence.